Research on Relationships Between Fluid Pressure and Technological Parameters, Shape of Cylindrical Part in Hydro Static Forming - Nguyen, Thi Thu; Nguyen, Dac Trung (Old Journal, 2018)
In sheet hydrostatic forming, accuracy of products depends on many technological parameters and shape of die, especially working fluid pressure plays very important role. Determination of this pressure is usually difficult, because it depends on the other parameters, such as blank holder pressure, workpiece material, geometrical shape and tightness of die, so on. This article deals with determination of relationship between forming pressure, blank holder pressure and radius of bottom die using experiments. The results of this study are the basis for further validating the quality and accuracy of product, as well as optimizing hydrostatic forming technology.